The Future of Rehabilitation: AI and the Transformation of Education in Prisons - Dr. Shilpa N. Gaikwad; Mr. Hakar Abdulkarim Findi; Dr. Sanket Charkha (The Bioscan, 2025)
This review article delves into the revolutionary possibilities of AI using artificial intelligence to change jail curricula. In doing so, it sheds light on the present state of prison education and the obstacles that prevent the efficient implementation of educational programs. Digital literacy tools, risk assessment algorithms, and e-learning platforms are just a few examples of the AI technologies covered in this article as it explores the role of AI in solving these problems. Some of the benefits of AI that are discussed include enhanced engagement, personalised learning experiences, and skill development that aligns with what is expected in the job market. Drawing on research on artificial intelligence in the fields of education, sports medicine, and rehabilitation, the article also provides a critical evaluation of the effects of AI-powered education on rehabilitation results in the Prison. We take a look at the long-term effects, such as better social reintegration, lower recidivism rates, and increased employability. In addition to discussing the theoretical and methodological obstacles to implementing AI-powered education programs in correctional systems, the article delves into the ethical considerations surrounding data privacy, algorithmic bias, and equitable access. The study ends by highlighting the need of resolving ethical and practical problems via strong governance regulations, techniques to mitigate prejudice, and strategic investments, and by highlighting the potential of AI to transform prison education and rehabilitation.